THE EFFECT OF SKILL AGILITY ON TEACHERS’ PERFORMANCE IN PUBLIC JUNIOR HIGH SCHOOLS IN SRAGI DISTRICT, PEKALONGAN REGENCY - Khelly Novi Susanti; Ghufron Abdullah; Qristin Violinda (SOSIOEDUKASI, 2026)
This study aims to analyze the effect of skill agility on teachers’ performance in public junior high schools in Sragi District, Pekalongan Regency. The study employed a quantitative approach with a descriptive correlational design. The population consisted of 173 teachers, with a sample of 121 respondents determined using the Isaac and Michael formula and proportional random sampling technique. Data were collected through a five-point Likert scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using simple linear regression after fulfilling prerequisite tests, including normality, homogeneity, and linearity. The results indicate that skill agility has a positive and significant effect on teachers’ performance (p < 0.05), with a contribution of 73.7%. This finding suggests that teachers’ ability to learn quickly, think flexibly, and adapt to change is a key factor in enhancing professional performance. The cognitive agility dimension was identified as the most dominant indicator in shaping skill agility. This study implies that efforts to improve teachers’ performance should focus on developing individual adaptive capabilities as a key competency in responding to the dynamic nature of education.